Major and minor minerals of ‘Sweetheart’ cherry stone from Cova da Beira - Antunes, P. (2020)
Nowadays customers demand objective and trustworthy information about the geographical origin of agricultural products. The mineral composition of agricultural products and its relation with their terroir has been shown to be a useful tool in differentiating commodities produced in a limited region and subjected to certain quality requirements. Cereja da Cova da Beira is the legal term used to denominate cherries produced in the Cova da Beira region (PGI - protected geographical indication) at central eastern part of Portugal, since 1996. In order to establish a methodology to certify its origin, the mineral profile of 'Sweetheart' cherry stone from Cereja da Cova da Beira , was studied. Quantification of major (Ca, Mg, K, P and Na) and minor elements (Cu, Fe Mn and Zn) of stones was carried out by inductively coupled plasma atomic emission spectrometry (ICP-AES). The results showed that, among major elements, Ca was the predominant mineral (1424.62 mg kg-1, dry weight), followed by K and Mg, presenting similar concentrations (1092.17 and 987.55 mg kg-1, respectively), P (271.10 mg kg-1), and Na (24.71 mg kg-1). Regarding micro elements, Mn showed the highest mean value (19.71 mg kg-1), followed by Fe (17.59 mg kg-1), and Cu and Zn with similar levels (7.61 and 6.73 mg kg-1, respectively). On the basis of chemometric pattern recognition procedures, the mineral content of agricultural products and its relation with their area of production can be a useful tool in differentiating commodities produced in a limited region and subjected to certain quality requirements.